INNOVATIVE CHANGES OF VALUES OF THE PUBLIC SECTOR IN THE CONTEXT OF UKRAINE'S EUROPEAN CHOICE - Valerii Osetskyi; Yevhen Hirnyk (Izdevnieciba "Baltija Publishing", 2017)
The article researches basic principles of innovation as a factor of social sector in the process of global peace and Ukrainian European integration. The study reveals the basic parameters of the phenomenon of innovation in the economy and public sector, allowing them to reach an understanding of the theoretical, institutional, value changes. Using historical and genetic approach. It also determines that the innovation factor for the public sector accounts for its effectiveness. The authors outline the problem of social oriented innovation, which together with commercial and non-profit sectors and the state find collaborative solutions to achieve social welfare. Particular attention is paid to the social demand, social needs, social commitment. In addition, attention is paid to the issue of the purpose of innovation - creating market efficiency by maximizing the use of new technologies. The paper proved that for a better understanding of the role and importance of innovation in the public sector, it is necessary to take into account the value factors in conjunction with the economic, social and political life made it possible growth.